MOF-Derived Tungstated Zirconia as Strong Solid Acids toward High Catalytic Performance for Acetalization. - Wang, P.; Feng, J.; Zhao, Y.; Wang, Shaobin; Liu, Jian (American Chemical Society, 2016)
A strong solid acid, tungstated zirconia (WZ), has been prepared first using tungstate immobilized UiO-66 as precursors through a "double-solvent" impregnation method under mild calcination temperature. With moderate W contents, the as-synthesized WZ catalysts possess a high density of acid sites, and the proper heat treatment also has facilely led to a bunch of oligomeric tungsten clusters on stabilized tetragonal ZrO2. The resultant solid acids show an improved catalytic performance toward the benzaldehyde's acetalization in comparison with traditional zirconium hydroxide-prepared WZ. Notably, due to large surface area and additionally introduced strong acid sites, the MOF-derived WZ catalysts afforded conversion up to 86.0%. The facile method endows the WZ catalysts with superior catalytic activities and excellent recyclability, thus opening a new avenue for preparation of metal oxide-based solid superacids and superbases.